Existence of Solutions of a Partial Integrodifferential Equation with Thermostat and Time Delay - Carlo Bianca; Luca Guerrini; Annie Lemarchand (Abstract and Applied Analysis)
This paper deals with the mathematical analysis of a retarded partial integrodifferential equation that belongs to the class of thermostatted kinetic equations with time delay. Specifically, the paper is devoted to the proof of the existence and uniqueness of mild solutions of the related Cauchy problem. The main result is obtained by employing integration along the characteristic curves and successive approximations sequence arguments. Applications and perspective are also discussed within the paper.